Adjuvanted Immunotherapy Approaches for Peanut Allergy - Johnson-Weaver, Brandi T.; Staats, Herman F.; Burks, A. Wesley; Kulis, Michael D. (Frontiers in Immunology, 2018)
Food allergies are a growing public health concern with an estimated 8% of US children affected. Peanut allergies are also on the rise and often do not spontaneously resolve, leaving individuals at-risk for potentially life-threatening anaphylaxis throughout their lifetime. Currently, two forms of peanut immunotherapy, oral immunotherapy (OIT) and epicutaneous immunotherapy (EPIT), are in Phase III clinical trials and have shown promise to induce desensitization in many subjects. However, there are several limitations with OIT and EPIT, such as allergic side effects, daily dosing requirements, and the infrequent outcome of long-term tolerance. Next-generation therapies for peanut allergy should aim to overcome these limitations, which may be achievable with adjuvanted immunotherapy. An adjuvant can be defined as anything that enhances, accelerates, or modifies an immune response to a particular antigen. Adjuvants may allow for lower doses of antigen to be given leading to decreased side effects; may only need to be administered every few weeks or months rather than daily exposures; and may induce a long-lasting protective effect. In this review article, we highlight examples of adjuvants and formulations that have shown pre-clinical efficacy in treating peanut allergy.